PENERAPAN MODEL RECIPROCAL TEACHING UNTUK MENINGKATKAN KETERAMPILAN MEMBACAPEMAHAMAN DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS RENDAH - Wahida Asni; Yenni Fitra Surya; Fadhilaturrahmi; Sumianto; Indriyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the reading comprehension skills of 16 third-grade students at UPT SDN 007 Sipungguk in the 2024/2025 academic year. This study uses Classroom Action Research (CAR) conducted in two cycles, each cycle consisting of two meetings with planning, implementation, observation, and reflection stages. Data collection techniques were carried out through observation, tests, and documentation. The results showed that before the intervention, only 6 students (37.5%) achieved learning completeness. After the Reciprocal Teaching model was applied in Cycle I Meeting I, there were 7 students (43.7%) who achieved completeness, then increased to 9 students (56.2%) in Meeting II. In Cycle II Meeting I, the number of students who achieved mastery increased to 11 (68.7%), and in Meeting II, it increased further to 13 students (81.2%). Based on these results, it can be concluded that the application of the Reciprocal Teaching model can help improve students' reading comprehension skills.